Reviving Social Europe: A critical assessment of EU social policy in the wake of multiple crises - Adrian Hawley (European Journal of Government and Economics (EJGE), 2023)
The concept of "Social Europe" encompasses the European Union's social policy framework. This paper argues that the financial crisis of 2007-2009, the subsequent Euro crisis, and the ensuing austerity measures diverted significant attention away from Social Europe. This neglect led to declining living standards, reductions in public services, and the emergence of critical challenges such as the gig economy. In recent years, the COVID-19 pandemic has further exacerbated these issues, prompting a renewed focus on Social Europe by EU institutions. This paper conducts a chronological analysis of recent legislative (acquis) and non-legislative (soft power) instruments implemented to address these challenges and assesses the prospects of Social Europe in the near term.
Keywords: H1; N44; 330; acquis; crises; European Union; Social Europe; soft power